The Effectiveness of Teaching Module in Sunday School Pre-Teen Class (Age 10 To 12) at The First Baptist Church in Mogoyunggung - Oei, Seren Shesien; Siang, Jhoni Lagun; Wuwung, Olivia Cherly (International Journal of Education, Information Technology, and Others, 2025)
This study aims to analyse the effectiveness of a specially designed Teaching Module for Sunday School Pre-Teen Class (Age 10 to 12) at the First Baptist Church in Mogoyunggung. Using a quantitative research methodology, a Pre-Test and Post-Test were performed to several Sunday School teachers as the primary users of the Teaching Module. The result of the Pre-Test that was conducted before the Teaching Module was given, showing an average score of 60,0 points. Then the Teaching Modules were given to the teachers, and the Post-Test was performed, and the average score round up to be 81,3 points. After collecting the data from the Pre-Test and Post-Test and calculating the average score, a T-Test using SPSS statistic software was conducted to statistically measure and evaluate the impact of the Teaching Module. The T-Test result indicated that a significant improvement in the teachers’ comprehension and knowledge, with a T-value of -8.000 and significance level of 0.008, which is below the 5% threshold (α = 0.05). These findings affirm that the Teaching Module significantly enhances the teachers’ pedagogical competencies and instructional effectiveness.